Measuring joy: happiness index and how APB brings it to life - UiTM, MITASA (Kesatuan Kakitangan Akademik UiTM (MITASA), 2025)
The Happiness Index is a data driven indicator that stands out, not because of its monetary value but because of the emotional value it brings. This index aims to assess the values of happiness, contentment, sadness, and a sense of well-being.